Which Surgeries Are the Best Choice for Chronic Pancreatitis: A Network Meta-Analysis of Randomized Controlled Trials - Mou, Yu; Song, Yi; Chen, Hong-Yu; Wang, Xing; Huang, Wei; Liu, Xu-Bao; Ke, Neng-Wen (Frontiers in Surgery, 2022)
Background: Surgery is an effective choice for the treatment of chronic pancreatitis (CP). However, there is no clear consensus regarding the best choice among the surgical procedures.The aim of this study is to conduct a network meta-analysis of randomized controlled trials comparing treatment outcomes to provide high-quality evidences regarding which is the best surgery for CP. Methods: A systematic search of the PubMed (MEDLINE), SCIE, EMBASE, CENTRAL and CDSR databases were performed to identify studies comparing surgeries for CP from the beginning of the databases to May 2020. Pain relief and mortality were the primary outcomes of interest. Results: Ten studies including a total of 680 patients were identified for inclusion. PPPD had a better postoperative short-term pain relief and quality of life (QOL), but a worse pancreatic exocrine function deficiency and high morbidity. Berne had a significant postoperative long-term pain relief and mortality with a lower risk of pancreatic exocrine function deficiency. Conclusion: The main surgical procedures including the PPPD, Beger procedure, Frey modification and Berne modification can efficaciously treat CP. The Berne modification may be the best choice for the treatment of CP with a better therapeutic effect and lower postoperative complications. However, when the CP patients have a mass in the pancreatic head which cannot be distinguished from pancreatic cancer, the only legitimate choice should be PPPD or classical pancreaticoduodenectomy.